Desensitization of the Cough Reflex Induced by Corticosteroids in Ovalbumin-Sensitized Rabbits During Artificial Limb Exercise - Valentin, Simon; Chenuel, Bruno; Demoulin-Alexikova, Silvia; Demoulin, Bruno; Gérard, Delphine; Foucaud, Laurent; Poussel, Mathias (Frontiers in Physiology, 2020)
Introduction: Cough is a major symptom frequently experienced during exercise, mainly in asthmatic patients. Inhaled glucocorticoids represent the keystone treatment in the management of asthma, but little is known about interactions between cough and exercise, especially in controlled patients. During exercise, cough reflex (CR) appears downregulated in healthy animal models whereas a lack of desensitization of CR has been shown in ovalbumin-sensitized animal models, mimicking asthmatic disease. Aims & Objectives: The goal of our study was to clarify the potential modulation of the CR induced by inhaled corticosteroids in ovalbumin-sensitized rabbits during artificial limb exercise. Materials & Methods: Seventeen ovalbumin-sensitized rabbits (OVA) were studied. Among them, 9 were treated with corticosteroids delivered intravenously (OVA-Corticoids). The ventilatory response to direct tracheal stimulation, performed at rest and during exercise, was determined to assess the incidence and the sensitivity of the CR. Broncho-alveolar lavage (BAL) and cell counts were performed to determine the level of airway inflammation. Exercise was mimicked by electrically-induced hindlimb muscular contractions (EMC). Results: Compared to rest values, EMC increased minute ventilation by 28% without any decrease in respiratory resistance (Rsr). Among 322 tracheal stimulations, 172 (53%) were performed at rest and 150 (47%) during exercise. The sensitivity of CR decreased during artificial limb exercise compared to baseline in OVA-Corticoids rabbits (p = 0.0313) while it remained unchanged in OVA rabbits (p = NS). Conclusions: Corticosteroids appear to restore the desensitization of the CR in ovalbumin-sensitized rabbits during artificial limb exercise, suggesting the potential role of airway inflammation in the pathophysiology of cough during exercise in asthmatics.